2021
DOI: 10.1186/s40798-021-00344-4
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Interval Training in Older Adults: a Scoping Review

Abstract: High-intensity interval training (HIIT) is an increasingly popular form of aerobic exercise which includes bouts of high-intensity exercise interspersed with periods of rest. The health benefits, risks, and optimal design of HIIT are still unclear. Further, most research on HIIT has been done in young and middle-aged adults, and as such, the tolerability and effects in senior populations are less well-known. The purpose of this scoping review was to characterize HIIT research that has been done in older adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 90 publications
(285 reference statements)
6
32
0
1
Order By: Relevance
“…However, high-intensity interval training (HIIT) appears to confer improvements commonly associated with both aerobic and resistance exercise training [ 22 ], whilst also addressing a commonly cited barrier to exercise uptake and adherence, “lack of time” [ 23 ]. Beyond “time”, older adults also frequently cite their age and “poor health” as barriers to exercise [ 24 ], despite a significant body of literature evidencing the benefits of all types of exercise training (aerobic: [ 25 , 26 ], resistance: [ 21 , 27 ], HIIT: [ 28 , 29 ]) for even the oldest old [ 30 ]. Further, the Generation 100 randomised control trial has demonstrated that older adults can perform both aerobic exercise and HIIT without strict supervision [ 31 , 32 ], suggesting that home-based, time-efficient HIIT without the need for specialist equipment may prove a promising strategy to improve the physiological resilience of older adults, especially at a time when access and desire to attend specialist exercise facilities (i.e., gyms and community classes) may be at an all-time low.…”
Section: Introductionmentioning
confidence: 99%
“…However, high-intensity interval training (HIIT) appears to confer improvements commonly associated with both aerobic and resistance exercise training [ 22 ], whilst also addressing a commonly cited barrier to exercise uptake and adherence, “lack of time” [ 23 ]. Beyond “time”, older adults also frequently cite their age and “poor health” as barriers to exercise [ 24 ], despite a significant body of literature evidencing the benefits of all types of exercise training (aerobic: [ 25 , 26 ], resistance: [ 21 , 27 ], HIIT: [ 28 , 29 ]) for even the oldest old [ 30 ]. Further, the Generation 100 randomised control trial has demonstrated that older adults can perform both aerobic exercise and HIIT without strict supervision [ 31 , 32 ], suggesting that home-based, time-efficient HIIT without the need for specialist equipment may prove a promising strategy to improve the physiological resilience of older adults, especially at a time when access and desire to attend specialist exercise facilities (i.e., gyms and community classes) may be at an all-time low.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the current results, a conclusion regarding which modality is most favorable to reduce fall risk in healthy older individuals cannot be reached. Yet, previous studies have shown that the cycle ergometer was the most common type of HIIT instrument used among older persons, followed by treadmill walking [59]. Furthermore, previous reviews recommended cycling (cycle ergometer) as an effective HIIT modality to improve cardiometabolic and cardiovascular health in older persons, including additional benefits in terms of accessibility, safety, and decreased stress on joints [59][60][61].…”
Section: Modalitymentioning
confidence: 99%
“…Most research on HIIT has been done in young and middle-aged subjects, and as such, the effects in senior populations are less known. Most common primary outcomes in the HIIT studies describe changes in cardiorespiratory fitness (such as VO 2 peak) as well as feasibility and safety of the protocols 49 . The transcriptomic and, more specifically, metabolomic changes induced by HIIT in old individuals are largely unknown, with few exceptions 50 where levels of several genes related to mitochondria, insulin signaling, and muscle growth were downregulated with age in skeletal muscle biopsies.…”
Section: Discussionmentioning
confidence: 99%